LEARNING TO SOLVE LOGICAL PROBLEMS IN A SECONDARY SCHOOL - Iskakova М.Т.; Orazbaeva А.К. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The formation of pupils’ mathematical knowledge by solving logical problems is one of the most popular in the modern world. Solving problems using a deep analysis of the set conditions of problems, without using memorable formulas for solving logical problems, helps to improve the thinking of. The tasks in this article are based on regional characteristics of some regions and cities of the Republic of Kazakhstan. The compiled tasks correspond to the content of education of the 6th grade of a secondary school. The mathematical model of a text problem, finding numbers by part, Euler-Venn diagram, proportion, calculation of the path, speed, and construction of the scheme contribute to the formation of navics for solving students ’ problems. Tasks related to the nature of their land arouse the interest of students and contribute to being a patriot of their country.